Molecular monitoring of the tumor load predicts progressive disease in patients with multiple myeloma after high-dose therapy with autologous peripheral blood stem cell transplantation - Lipinski, Emanuel; Cremer, Friedrich Walter; Ho, Anthony Dick; Goldschmidt, Hartmut; Moos, Marion (Bone marrow transplantation, 2001)
The clinical relevance of the assessment of minimal residual disease (MRD) in patients with multiple myeloma (MM) to predict disease recurrence has not been proven. In the present study, we retrospectively analyzed the tumor load in peripheral blood (PB) and bone marrow (BM) samples of 13 patients with MM both in remission after high-dose therapy (HDT) with autologous PBSC transplantation (PBSCT) and at the time of progressive disease (PD). For six patients, subsequent samples obtained in remission could be included in the study. Tumor cells were assessed by means of quantitative PCR with allele-specific oligonucleotides (ASO-qPCR) based on the method of limiting dilutions. PD was documented with ASO-qPCR in BM samples (median concentration of tumor cells in remission vs at PD: 0.18% vs 4.6%) representing a significant increase by a median factor of 8.7. In PB, the median tumor load was 799 cells/ml in remission and 23 400 cells/ml at PD. With a median factor of 45, the increase was much more pronounced. Comparing the results of the molecular monitoring in PB with those of the determination of the monoclonal protein, routinely applied as parameter for the course of the disease, revealed a superiority of the molecular monitoring because of the significantly higher increase in the tumor load. Analyzing the subsequent remission samples showed an increase of the malignant cells in four out of six PB samples and in all four BM samples available, indicating the potential of ASO-qPCR for an early PD recognition. Bone Marrow Transplantation (2001) 28, 957-962.